Literasi Investasi Keuangan Bagi Mahasiswa Ikopin University Strategi Investasi Keuangan Melalui Koperasi, Peluang dan Tantangan - Savitri Dewi, Lely (LPPM Universitas Koperasi Indonesia, 2024)
Basically, investment activities are divided into two types, namely investment activities in the financial asset sector, namely in the capital market and money market, and investment activities in the real assets sector. In this literacy activity, participants are directed to understand and recognize financial asset investment products, and investment techniques. and various benefits of investing. The focus of this literacy is also related to the role of cooperatives as the community's choice, especially members, in their capacity as an investment vehicle, especially in Savings and Loans Cooperatives. This literacy activity is the result of the performance of the Management and Accounting Student Association in collaboration with LPPM Ikopin University and Allo Bank Bandung. Held at the Ikopin University campus on November 28, 2023